Shades of green and transformational leadership: Predicting employees' green creativity and green work engagement at work - Shavneet Sharma; Norah Albishri; Hina Zafar; Abhishek Bhushan Singhal; Gurmeet Singh (Acta Psychologica)
As the tourism sector faces increasing pressure to reduce its environmental footprint, employees are emerging as vital agents of sustainable transformation. Employing the stimuli-organism-response (SOR) framework and data collected from 324 employees, this study investigates the psychological processes underlying green work engagement. Covariance-based structural equation modeling revealed that both green attitudes and resource commitment are significant predictors of individual green values, which, in turn, are positively associated with green creativity and work engagement. Moreover, green creativity was found to mediate the relationship between individual green values and work engagement. In contrast, the moderating effects of green intrinsic motivation on these relationships were not supported. These findings extend the understanding of green organisational behaviour and sustainability in the hospitality and tourism context by revealing novel links among green attitudes, resource commitment, and leadership practices. It adds to the discourse on the roles of intrinsic motivation and individual green values in enhancing engaged and innovative environmental practices. These results offer valuable insights for policymakers, environmental researchers and industry practitioners looking to increase their sustainable performance.